Friends forever [compact disc, unabridged] : a novel - Steel, Danielle (Brilliance Audio, 2012)
Two girls and three boys meet at school as young children. Together, they become an inseparable group and lean on one another through childhood and adolescence. But when the tight-knit group graduates and scatters to different colleges, their lives diverge dramatically, and some of the friends are lost forever. Those who remain will struggle to understand that even bonds that once seemed unbreakable are not proof against tragedy, but that they can also transform into something new.